1999
DOI: 10.1159/000016308
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome Inhibitors Induce p53/p21-Independent Apoptosis in Human Glioma Cells

Abstract: The proteasome is a multiprotein complex involved in the degradation of ubiquitinated proteins. Three proteasome inhibitors, calpain inhibitor I, lactacystin and MG132, induced apoptosis in several human malignant glioma cell lines. Although proteasome inhibitors induced p53 accumulation in a cell line retaining wild-type p53 activity, p53 activity was dispensable for apoptosis since transdominant-negative p53 abrogated p53-dependent p21 induction but did not modulate apoptosis. Further, p21 was induced by hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
39
0
1

Year Published

2000
2000
2006
2006

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 16 publications
7
39
0
1
Order By: Relevance
“…Although PIs have been shown to induce p53-independent apoptosis in glioma cells (Wagenknecht et al, 1999;Yin et al, 2005), the majority of reports suggest that PIs induce a p53-dependent form of apoptosis in most cancer cell types, such as leukemia cells (Shinohara et al, 1996;Masdehors et al, 2000), as well as melanoma and myeloma cells (Qin et al, 2005). Consistent with previous studies we observed a prominent increase of p53 levels, which was associated with transcriptional activation of the proapoptotic BH3-only gene PUMA.…”
Section: Discussionsupporting
confidence: 90%
“…Although PIs have been shown to induce p53-independent apoptosis in glioma cells (Wagenknecht et al, 1999;Yin et al, 2005), the majority of reports suggest that PIs induce a p53-dependent form of apoptosis in most cancer cell types, such as leukemia cells (Shinohara et al, 1996;Masdehors et al, 2000), as well as melanoma and myeloma cells (Qin et al, 2005). Consistent with previous studies we observed a prominent increase of p53 levels, which was associated with transcriptional activation of the proapoptotic BH3-only gene PUMA.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, both the GBM cell lines and explants cultured with PS-341 accumulated in the G2/M phase associated with their increased levels of p21 WAF1 , p27 KIP1 , and cyclin B1. Previous studies using other proteasome inhibitors found that expression of p21 WAF1 and p27 KIP1 increased in glioma cells (Kitagawa et al, 1999;Wagenknecht et al, 1999). Furthermore, we found that levels of CDK2 and CDK4, as well as, E2F4 decreased ( Figure 4) consistent with the cells exiting the cell cycle.…”
Section: Discussionsupporting
confidence: 77%
“…In vitro screening data using a panel of 60 human tumors cell lines indicated that PS-341 has significant growth inhibitory activity against a wide variety of tumors . Other proteasome inhibitors, such as the calpain inhibitor, lactacystin, MG132, and AcLLNal, also inhibit glioma cell growth (Kitagawa et al, 1999;Wagenknecht et al, 1999;Tani et al, 2001). However, little has been reported of the effect of PS-341 on GBM cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10][11][12][13][14] On the other hand, numerous inhibitors of proteolysis induce apoptosis. [15][16][17][18][19][20][21][22][23][24] Apoptosis can be induced by a variety of stimuli, including the p53 tumor suppressor. 25 Besides wt p53, other tumor suppressors such as p27 26 and BRCA1 27 can induce apoptosis.…”
Section: Introductionmentioning
confidence: 99%